#TITLE_ALTERNATIVE# - FEBRINA (NIM: 12011062), FIDIYANTI
This study discusses estimation, mechanism, and distribution of the overpressure in Sepinggan Field, Kutai Basin, East Kalimantan. Of the 121 wells examined, there is 1 well showing the indications of overpressure, i.e. well S00090. Overpressure characteristics in this field analyzed from pore pressure data, drilling reports, wireline logs, geochemistry data, and mudweight. To determine the distribution of the overpressure in the Sepinggan Field, the data of seismic wave velocity is used from one well. Based on the evidence in Sepinggan Field (S00090), it is known that the top overpressure is located at the depth of 10100 ft. Based on overpressure modeling from seismic wave velocity data, the top of overpressure is shallower in the Northwest Sepinggan Field, while it is deeper in the Northeast Sepinggan Field. The top of overpressure follows the morphology of Yakin Sequence. The estimated top of overpressure in the well S00090 is 9854.46 psi at the depth of 11814 ft. The mechanism generating overpressure in the research area is non loading (transformation smectite into illite minerals) and loading (disequilibrium compaction).